An Innovative Diagnostic Strategy for Malignant Pleural Effusion Using Discontinuous Gradient Centrifugation - Jin-xin Zhu; Lei Yuan; Yong-tao Zhan; Ying-jie Li; Hao-ming Xia; Ming Jiang; Xiang Ao; Jie Zhou; Qian Wang; Dong-hui Zhang; Zhi-jie Zhang; Hong-sheng Li; et al. (Archives of Pathology & Laboratory Medicine, 2026)
Context.— Malignant pleural effusion (MPE) is a common cancer metastatic complication, and distinguishing it from benign effusions is critical for treatment. Cytology is central to MPE diagnosis, but inflammatory and reactive mesothelial cells often obscure malignant cells, limiting accuracy. Although liquid-based cytology (LBC) improves specificity over conventional smears, its use is constrained by specialized equipment requirements. Objective.— To investigate a novel discontinuous gradient centrifugation (DGC) technique for improving the diagnostic efficiency of MPE. Design.— We prospectively analyzed 55 pleural effusion samples (September 2021–April 2023) using DGC and LBC, with cytoblock paraffin embedding and immunohistochemistry as the reference standard. Results.— Immunohistochemical staining classified 24 cases as benign and 31 as malignant. Class IA was found in 27 (49.09%), IB in 2 (3.64%), IC in 0 (0%), II in 2 (3.64%), and III in 24 (43.64%) cases via DGC; with LBC, class IA was in 9 (16.36%), IB in 7 (12.73%), IC in 8 (14.55%), and II in 8 cases. (14.55%). DGC had 1 false-positive and 3 false-negative results, whereas LBC had 2 false positives and 9 false negatives. Compared with LBC, DGC showed significantly higher sensitivity (90.32% versus 70.97%, P = .001), negative predictive value (88.46% versus 70.97%, P = .003), and overall accuracy (92.72% versus 80.0%, P = .007). Receiver operating characteristic curve analysis revealed a significantly larger area under the curve for DGC (0.931 [95% CI, 0.873–0.989] versus 0.813 [95% CI, 0.704–0.922]). Conclusions.— DGC is an innovative, highly accurate method for MPE detection, outperforming LBC in clinical practice.